Reliability and validity of the Greek version of Kogan's Old People Scale - Sourtzi, Panayota A.; Kalokerinou, Athena; Lemonidou, Chryssoula; Lambrinou, Ekaterini (My University, 2005)
Aims and objectives. The aim of this study was to test the psychometric properties – validity and reliability – of the Greek version of Kogan's Old People scale. Background. The ageing of the population in most of the developed world and in Greece, challenge-nursing care, therefore, nursing education needs to be updated accordingly. Until today there have been no studies in Greece in relation to student nurses' attitudes towards older people. To have a reliable questionnaire for measuring a Greek population's attitudes towards older people the Kogan's Old People Scale was translated into Greek. Design. The study was designed as a cross-sectional survey. The main reason for choosing a cross-sectional survey was the time limits for the study. A sample of 390 nursing students in Athens participated in the study. Methods. A questionnaire was given to the students, which included the Kogan's Old People Scale. Results. Results showed Cronbach's alpha coefficient 0·73 for the OP− scale and 0·65 for the OP+ scale, which are comparable to published studies until today. The six-factor solution explains the 41·5% of the variance in the sample. The scale was also found to differentiate between first and final year students on how their education in nursing is influencing their attitudes towards the older people. Conclusions. Reliability and validity supported the Greek version of the Kogan's Old People Scale as a reliable instrument. Its use in evaluating Greek nursing education programmes could help in preparing nurses capable of meeting the needs of older people. Relevance to clinical practice. Nursing education – basic and lifelong – needs to be updated in order to respond to the needs of older people and a reliable instrument can help to evaluate it.
Keywords: Attitudes; Elder care; Kogan's Old People Scale; Nurse education